Analysis of the Implementation of Regional Regulation Number 13 of 2015 of Balikpapan City concerning Waste Handling from the Perspective of Fiqh Siyasah - Sitorus, Muhammad Rafii (Jurnal Sosial Teknologi, 2025)
The increase in the population of Balikpapan City, which will reach 738,532 people in 2024, produces a volume of up to 500 tons of waste per day. This study aims to analyze the implementation of Regional Regulation Number 13 of 2015 concerning waste management from the perspective of fiqh siyasah. The research method uses a qualitative approach by collecting data through observation, interviews, and documentation of related agencies and residents of Balikpapan City. The data was analyzed using a qualitative descriptive method based on the rules of fiqh siyasah. The results showed that 88.5% of respondents supported the regulation of restricting waste disposal time (18.00-06.00 WITA) and predetermined waste disposal sites. However, there are implementation obstacles in the form of ignorance of some residents (16.7%), the distance of the garbage cans, and the condition of the garbage cans that are often full. From the perspective of fiqh siyasah, this regulation is in line with Islamic principles of environmental cleanliness and the government's authority in regulating the benefit of the people. The volume of waste has increased significantly from 358 tons/day (2020) to 500 tons/day (2024). DLH provides 417 polling stations spread across 6 sub-districts with a 2-shift transportation system. The research concluded that the implementation of the Regional Regulation is quite compatible with the support of the majority of residents, but improvements are needed in the socialization of regulations and the addition of supporting facilities.